A Highly Specific Antibody-Based Assay for Nipah Virus AlphaLISA Detection - Xuyang Sun; Qingyu Lv; Wenhua Huang; Xinran Zhang; Huiqi Duan; Yuhao Ren; Xiaojing Zhang; Yongqiang Jiang; Ruili Zhao; Shaolong Chen (Viruses)
Nipah virus (NiV) is an emerging zoonotic pathogen whose surface glycoprotein (G)-mediated host cell invasion mechanism leads to fatal encephalitis in infected patients (case fatality rate 40–75%). Given the limitations of existing diagnostic technologies, such as low sensitivity and prolonged processing times, we prepared an anti-NiV-G monoclonal antibody to establish a novel Amplified Luminescent Proximity Homogeneous Assay (AlphaLISA) detection system. Firstly, five high-affinity anti-NiV-G monoclonal antibodies were screened from the spleens of immunized mice by flow cytometry-single-cell cloning technology. The reaction system was further optimized, and the optimal dilution ratio of antibody-conjugated receptor microspheres, biotinylated antibodies, and donor microspheres was screened, and the AlphaLISA detection platform was successfully constructed. The detection sensitivity of NiV-G protein was 0.024 ng/mL (41.7 times higher than that of conventional ELISA), the coefficient of variation was <9.5%, and the repetition was good. It showed good specificity in the detection of 5 zoonotic viruses, including Japanese encephalitis virus and Zika virus. At the same time, this method is less disturbed by human serum, and the detection time is less than 30 min, showing a good clinical application prospect.